The Role of International Norm-Making and Law in Defining INGOs' Legal Subjectivity - Elnara Mirzayeva (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
This manuscript analyzes the contemporary position of international non-governmental organizations (INGOs) within the framework of international law by emphasizing the disparity between their growing practical significance and their unsettled legal status. The study aims to examine the role of INGOs in international relations, identify the legal and institutional challenges surrounding their international legal recognition, and advance a reasoned justification for recognizing their international legal personality. To illustrate national perspectives on this issue, the research incorporates selected aspects of Azerbaijan’s experience. Using an institutional research method, the study evaluates prevailing doctrinal approaches to the legal subjectivity of INGOs and identifies the core elements of their international legal status. The findings demonstrate that international law does not formally recognize INGOs as subjects in the strict legal sense. However, given their expanding functions, broad operational reach, and increasing influence in international governance, the study argues that the international legal system must develop a normative framework to regulate their status. The principal justification for recognizing the legal subjectivity of INGOs rests on the persistent imbalance between their actual role in international relations and the absence of corresponding legal recognition.